Pelaksanaan Evaluasi Pembelajaran Daring Selama Pandemi Covid-19 - Aria Indah Susanti; Dwi Sari Ida Aflaha (SAP (Susunan Artikel Pendidikan), 2022)
The purpose of the research is to see the implementation of student learning evaluations at the elementary, middle and high school levels during the covid-19 pandemic. The researchers conducted research from May to June 2022 using descriptive qualitative methods, namely collecting research data to obtain relative, theoretical truth, and using interpretation and understanding. Research data were collected through a questionnaire presented in the form of a Likert scale and open-ended questions with several options for data collection. The conclusion obtained through the analysis of questionnaire data on the implementation of student learning evaluations with elementary, middle, and upper level educator respondents, namely during online learning during the Covid-19 pandemic, most educators have carried out learning evaluations using various online media as well. In general, the answers given by respondents are still constrained by the availability of media and internet networks if the evaluation of learning outcomes is carried out online. The other alternatives used for learning evaluation also have not given satisfactory results due to limited facilities and the lack of readiness of educators and students.